Geochemical characterization of n-alkanes and polycyclic aromatic hydrocarbons in water and sediment from new calabar river - Obudu Mosephni Brother; Kpee Friday; Nna Prince Joe (Research Parks Publishing LLC, 2021)
Geochemical characterization of polycyclic aromatic hydrocarbon and n-alkanes in sediment and water from New Calabar Rivers was carried out using gas chromatography – Flame Ionization Detector (FID). A total of twenty-six (26) n-alkanes were quantified and identified for water sample whereas the sediment sample recorded a total of twenty-five (25) n-alkanes. The n-alkane concentrations varied between 0.48-43.80 for sediment samples and 0.27-22.0 for water sample. The study involves the use of some geochemical parameters such as CPI, , Paq LHC/SHC for characterization of n-alkanes. The n-alkane in sediment and water from the study area ranged from with at suggesting mixed contribution of terrestrial plant wax and petroleum/microbial sources of organic matter. < 25 are indicative of petroleum and microbial source input while > 25 reflects the incorporation of higher plant wax. The PAHs detected and quantified in the samples are the regular PAHs found in the ecosystem and are formed from anthropogenic sources. Based on the study, it was discovered that water and sediment from the study area had variable contributions to n-alkanes and PAHs predominantly petroleum inputs as the secondary source (allochthonous) continental inputs and microbial inputs from organic matter such as macrophytes and phytoplanktonic derived organic matter as its primary source (autochthonous) planktonic inputs.